NILAI-NILAI PENDIDIKAN BUDI PEKERTI LUHUR DALAM CERITA RAKYAT DAERAH LAMONGAN - Hendrik Furqon; Ernaningsih Ernaningsih (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
The purpose of this research is to focus on the discovery (1) the educational values of noble character contained in Lamongan folklore (2) the narrative structure of the text of the Rakyat Lamongan story. The method used in this research is qualitative descriptive with an educational value approach in literary works (pragmatic). The data in this study are data about (1) the values of noble character education contained in Lamongan folklore and (2) the narrative structure of the text of the Rakyat Lamongan story. Data sources are obtained from documentation and interviews. The data collection techniques are carried out with documentation and interviews. Data analysis techniques use interactive techniques. Data validation uses triangulation, both triangulation of theories, data, and methods. The findings of the research can be described include: (1) the value of noble character education contained in Lamongan folklore includes the values of partners, traditional values, happy values, and, upeksa values. , (2). Narrative structure of the text of Rakyat Rakyat Lamongan.